2016
DOI: 10.4081/reumatismo.2016.844
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic granulomatous mastitis with erythema nodosum and polyarthritis

Abstract: summary A 25 year-old woman presented with a painful mass in the left breast, polyarthritis and erythema nodosum. Fine needle aspiration cytology led to a diagnosis of granulomatous mastitis. Oral prednisolone rapidly improved the arthritis and the erythema nodosum. Granulomatous mastitis is a very rare, chronic inflammatory disease and only ten patients with granulomatous mastitis with erythema nodosum and polyarthitis have been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Although cases of IGM complicated solely by EN are very rarely reported, to our knowledge, only ten other cases of IGM complicated by both arthritis and EN have been previously reported. All the patients received immunosuppressive treatment (9,10). It should be considered that IGM and EN may have similar autoimmune mechanisms during their development.…”
Section: Discussionmentioning
confidence: 99%
“…Although cases of IGM complicated solely by EN are very rarely reported, to our knowledge, only ten other cases of IGM complicated by both arthritis and EN have been previously reported. All the patients received immunosuppressive treatment (9,10). It should be considered that IGM and EN may have similar autoimmune mechanisms during their development.…”
Section: Discussionmentioning
confidence: 99%
“…The EN is a rare systemic symptom of IGM, first described by Adams et al in 1987 8 . The EN and IGM association is rare, reported with case reports and series 9‐15 . Additionally, to the best of our knowledge, it is the only systemic and extra‐breast finding of IGM.…”
Section: Introductionmentioning
confidence: 96%
“…8 The EN and IGM association is rare, reported with case reports and series. [9][10][11][12][13][14][15] Additionally, to the best of our knowledge, it is the only systemic and extra-breast finding of IGM. However, no studies were reported before elaborating the significance of both entities' coexistence on the severity of IGM and response to conventional treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, autoimmunity and immune dysregulation have been emphasized, but studies on this subject are limited. Some patients with IGM respond well to immunosuppressive drugs such as steroids and methotrexates; the presence of extramammary findings likes erythema nodosum or arthritis in some patients and some recent studies, although limited, suggest that more emphasis should be given to autoimmunity and immune dysregulation in IGM [3][4][5][6][7][8][9][10][11][12][13]. The aim of our study was to investigate the number of T and B lymphocytes and changes in NK and NKT cells in IGM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Remission and relapse of IGM in some patients with rheumatologic findings, such as arthritis and/or erythema nodule, suggest autoimmunity and immune dysregulation [5][6][7][8][9][10][11]. Erhan et al [12] found T lymphocyte domination in the tissue of IGM patients.…”
Section: Introductionmentioning
confidence: 99%